EFFECT OF ASCORBIC ACID AND ALPHA TOCOPHEROL SUPPLEMENTATION ON ACUTE RESTRAINT STRESS INDUCED CHANGES IN TESTOSTERONE, CORTICOSTERONE AND NOR EPINEPHRINE LEVELS IN MALE SPRAGUE DAWLEY RATS - Lodhi, Ghulam Mustafa; Latif, Rabia; Hussain, Muhammad Mazhar; Naveed, Abdul Khaliq; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Stress of various origins suppresses male reproductive functions through releasing stress hormones. Antioxidant like ascorbic acid (AA) and alpha tocopherol (AT) have been thought to protect the body against stress induced damage. Whether, these antioxidants confer protection against the stress induced increased levels of corticosterone and nor-epinephrine, and decreased testosterone secretion have been investigated in this study. Methods: This quasi experimental study was carried out at the Department of Physiology, Army Medical College Rawalpindi in collaboration with National Institute of Health, Islamabad during March to September 2009. Eighty male Sprague Dawley rats were divided into five groups with sixteen rats in each group. Group-I served as the control without stress while group-II was exposed to restraint stress for 6 hours, group-III was administered AA, group-IVAT and group-V was supplemented with both the antioxidants along with standard diet for one month. All antioxidant supplemented groups were exposed to restraint stress for 6 hours. Immediately after the stress episode, blood sample was obtained for the assay of serum testosterone, serum corticosterone by EIA and plasma nor-epinephrine levels by ELISA. Data were analyzed on SPSS-13 and p-value less than 0.05 was considered significant. Results: Acute restraint stress resulted in a statistically significant rise in corticosterone and nor-epinephrine levels and fall in serum testosterone levels. AA supplementation for one month revealed insignificant changes in stress induced hormonal parameters. AT alone and in combination with ascorbic acid prevented the fall in testosterone level as well as rise in corticosterone, however nor-epinephrine levels remained unchanged. Conclusion: Supplementation with AT alone or in combination with AA prevent reduction in testosterone and rise in corticosterone levels while keeping the nor-epinephrine levels unchanged after acute restraint stress in Sprague Dawley rats. Keywords: Acute restraint stress, testosterone, corticosterone, nor-epinephrine, ascorbic acid, alpha tocopherol